2017
DOI: 10.1093/trstmh/trx033
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of West Nile virus in West Bengal, India: a new report

Abstract: The serological and molecular approaches have clearly established the emergence of WNV in West Bengal. Hence, for proper case management, detection of WNV in common febrile illness is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…and Aedes spp. are mainly responsible for the transmission of the virus [8]. Depending on the season, migratory birds annually overfly countries in both the Northern and Southern hemisphere [9], thus playing an essential role in the spread of WNV in Asia, Africa, and Europe [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Aedes spp. are mainly responsible for the transmission of the virus [8]. Depending on the season, migratory birds annually overfly countries in both the Northern and Southern hemisphere [9], thus playing an essential role in the spread of WNV in Asia, Africa, and Europe [1].…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, it has been reported that 0.3% of migratory wild birds had immunoglobulin against WNV [16]. WNV seroprevalence was reported as being 11.6% [17] to 14.5% [8] in humans and 1.6% in wild residents and migratory birds [18] in India. Moreover, WNV was detected in humans and horses in Pakistan [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of WNV on human and animal health increased dramatically during the last two decades, particularly in the United States of America, with more than 2,000 deaths between 1999 and 2018 (24), and in Europe (25,26). Human WNV cases were also reported in several Asian countries (27)(28)(29)(30) but little is known about its epidemiology and its potential impact on health in this continent.…”
mentioning
confidence: 99%
“…In India, asymptomatic infections had been reported for many years with isolations from mosquitoes and humans, especially in South India. Febrile illness in epidemic form and clinically overt encephalitis patients has been observed in Assam, North east (62), and Kerala, Southern regions of India (3,13), and recently, in West Bengal and Madhya Pradesh states (64,129).…”
Section: Morbidity and Variation Of Wn And Den Virus Infectionsmentioning
confidence: 99%